An Investigation of Young Childrens Politeness Principle - Liya Umaroh; Neni Kurniawati; Christy Atika Sari (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
Politeness principle is part of pragmatics study, and it takes place as the youngest in a branch of linguistics. Pragmatics focuses in relation to situations of speech that is influenced by the speakers, addressees and context. By the time childrens politeness getting lesser because of the lack on parental guidance and assistance to the children on the use of smart phones, television program and through internet. Parents tend to be busy either with their own smart phones or their job respectively. Children on preoperational phase of 2-7 years of age need assistance and also emphasized on politenss compensation from their parents. In this phase the child is so easy to absorb information, mimicking all the good behavior of the family environment or the surrounding community.This study uses qualitative descriptive method supported by distributing questionnaires and interview as an instrument to collect data and will be used as a main data. Samples were children 2-7 years old who are in school Yayasan Bina Amal at Jl. Kyai Saleh No. 8 Mugassari city of Semarang. They are students who are in Kindergarten and Primary school 1.Stage activities are starting with the implementation of the pre field, field, analysis and preparation of reports. The purpose of this study is to see the extent to which children in the age in politeness compensation preoperational as the development of pragmatic science studies. The result is the use Leech politeness principle got quite fulfilled. Discretion maxim usage among others (12%), politeness maxim (10%), praise maxim (20%), modesty maxim (18%), loyalty maxim (20%), sympathy maxim (20%). In addition to the percentage of the use in maxim, the closeness between mother and child greatly affect in parenting and the impact on the ability to perform speech.